HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA - Syahniar Syahniar; Besti Nora Dwi (Universitas PGRI SUMATERA BARAT, 2017)
This research is motivated by the problems were many students are having problems of mathematics learning outcomes at schools. Many students did not complete the study of mathematics. The research aims to describe (1) learning motivation,(2) the correlation of learning motivation and student learning outcomes.This study used a descriptive correlational quantitative method. The study population were students of SMAN 1 Rambatan School Year 2014/2015 522 people the sample of 208 people, which is selected by stratified random sampling technique. The instrument was a questionnaire with reliability of 0.971 (motivation to learn). Data have analyzed with descriptive statistics,simple linear regression and multiple regression.The research result showed that (1) students' motivation were at high enough category,(2) there was a correlation of learning motivation the learning outcomes of student.Keyword : Learning Motivation, Mathematics Learning Outcomes.